2007
DOI: 10.3846/1648715x.2007.9637558
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Current Trend in Mortgage Valuation Practice in Nigeria

Abstract: The emerging concern on the reliability of property valuations coupled with the attendant consequences of growing number of distressed banks in Nigeria necessitate this study. Therefore, the study examined the mortgage valuation process including sources of valuation instructions, bases and methods being adopted and their implications on lending decisions and valuation profession in the study area. To accomplish the study, questionnaires were randomly administered on samples of estate surveying and valuation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Also Aluko (2007) carried out further study of the mortgage valuation process in Lagos metropolis. In the study, the author administered questionnaires randomly on Estate Surveying and Valuation firms practising within the study area as well as the lending institutions with the intention of ascertaining whether the contents of mortgage valuation reports and estimates being given by the valuers meet the expectations of the lending institutions as well as meeting the standards set for such valuation by the profession.…”
Section: The Study Areamentioning
confidence: 99%
“…Also Aluko (2007) carried out further study of the mortgage valuation process in Lagos metropolis. In the study, the author administered questionnaires randomly on Estate Surveying and Valuation firms practising within the study area as well as the lending institutions with the intention of ascertaining whether the contents of mortgage valuation reports and estimates being given by the valuers meet the expectations of the lending institutions as well as meeting the standards set for such valuation by the profession.…”
Section: The Study Areamentioning
confidence: 99%
“…Oyetunji and Oyetunji-Olakunmi (2017) assessed viability appraisal practice in Lagos and concluded that the application of appropriate modern appraisal techniques is a difficult task for estate surveyors and valuers in the area. Aluko (2007) found that most estate surveying and valuation firms in Lagos were not reflecting appropriate basis, methods and information contents in their mortgage valuation reports. This form of practice will certainly result in inconsistent and inaccurate valuations.…”
Section: Methods Of Valuationmentioning
confidence: 99%
“…There are several issues involved in secured lending valuations. Principal among these have been identified by a plethora of studies (Crosby, 2000;Aluko, 2007) to include the use of wrong valuation bases, data and methods, resulting in inaccurate property valuations. The nature of these issues in the context of secured lending valuations are discussed as follows:…”
Section: Issues In Secured Lending Valuationsmentioning
confidence: 99%
“…Some DMBs however require rental value (RV) in addition to MV and FSV (Babatunde, 2011;2017). Aluko (2004Aluko ( , 2007, Ogunba (2004), Oluwunmi et al (2011Oluwunmi et al ( , 2013, Ishaya et al (2012) and Adegoke et al (2013) were some of the studies that investigated the needs and satisfaction of DMBs in SLV reports in Nigeria. They held divergent views on the appropriateness of the reports.…”
Section: Literature Reviewmentioning
confidence: 99%